13 CO/C 18 O gradients across the disks of nearby spiral galaxies - Jiménez-Donaire, Maria Jesús; Cormier, Diane; Bigiel, Frank (The astrophysical journal. Part 2, Letters, 2017)
We use the IRAM Large Program EMPIRE and new high-resolution ALMA data to measure 13 CO(1-0)/C 18 O(1-0) intensity ratios across nine nearby spiral galaxies. These isotopologues of 12 CO are typically optically thin across most of the area in galaxy disks, and this ratio allows us to gauge their relative abundance due to chemistry or stellar nucleosynthesis effects. Resolved 13 CO/C 18 O gradients across normal galaxies have been rare due to the faintness of these lines. We find a mean 13 CO/C 18 O ratio of 6.0 ± 0.9 for the central regions of our galaxies. This agrees well with results in the Milky Way, but differs from results for starburst galaxies (3.4 ± 0.9) and ultraluminous infrared galaxies (1.1 ± 0.4). In our sample, the 13 CO/C 18 O ratio consistently increases with increasing galactocentric radius and decreases with increasing star formation rate surface density. These trends could be explained if the isotopic abundances are altered by fractionation; the sense of the trends also agrees with those expected for carbon and oxygen isotopic abundance variations due to selective enrichment by massive stars.
Im Titel sind die Zahlen "13" und "18" hochgestellt
13CO/C18O gradients across the disks of nearby spiral galaxies
Gesehen am 25.10.2017